Faces of Muhammad - Moiz Mohammed (International Institute of Islamic Thought, 2020)
John Tolan’s Faces of Muhammad takes us on a journey through European perceptions of the Prophet of Islam. In European biographical literature, Muhammad took on various roles—initially almost exclusively malignant but gradually incorporating a positive assessment as well. The works of predecessors were integral to these writings, which meant that tropes developed over centuries had a durable quality. At the same time, reformist and revisionist thinkers reconstructed these tropes into polemical critiques of their own. In this way, exploring the reception of Muhammad since the twelfth century helps us understand modern discourses on religion.